2019
DOI: 10.3389/fgene.2019.00078
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-coding RNA MEG3 Attenuates the Angiotensin II-Induced Injury of Human Umbilical Vein Endothelial Cells by Interacting With p53

Abstract: Angiotensin II (Ang II)-induced damage to endothelial cells (ECs) plays a crucial role in the pathogenesis of cardiovascular disease. This study aimed to investigate the role of maternally expressed gene 3 (Meg3) in endothelial cell injury. A lncRNA human gene expression microarray analysis was used to identify differentially expressed lncRNAs in human umbilical vein endothelial cell (HUVECs). Cell viability, apoptosis, and migration were then assessed Ang II-treated HUVECs. qRT-PCR and western blotting were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…Ang II plays a role in endothelial dysfunction and it induced endothelial dysfunction is closely associated with cardiovascular diseases [ 16 ]. Previous studies have shown that Ang II-induced endothelial dysfunction has been used in hypertension models [ 17 , 18 ]. Autophagy plays a protective effect against endothelial injury by degrading damaged proteins and organelles and recycling the components for use in subsequent cellular processes [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ang II plays a role in endothelial dysfunction and it induced endothelial dysfunction is closely associated with cardiovascular diseases [ 16 ]. Previous studies have shown that Ang II-induced endothelial dysfunction has been used in hypertension models [ 17 , 18 ]. Autophagy plays a protective effect against endothelial injury by degrading damaged proteins and organelles and recycling the components for use in subsequent cellular processes [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, stimulation of HUVECs with Ang II is a reliable model to simulate vascular endothelial injury in vitro . In previous studies, the concentration and dose time of Ang II in an in vitro model were different ( 29 , 30 ). As presented in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…There are already some studies revealed that the relationship between the lncRNA and the vascular endothelial cells injury. For instance, the lncRNA Meg3 was consider as a protective element during the injury process of the vascular endothelial cells [23]. However, the lncRNA ZEB1-AS1 enhanced the oxidative low-density lipoprotein induced damage of the vascular endothelial cells [24].…”
Section: Discussionmentioning
confidence: 99%